Nitrogen fertilization and maturity influence the phenolic concentration of wheat grain (Triticum aestivum). Issue 1 (12th January 2015) - Stumpf, Beate; Yan, Feng; Honermeier, Bernd
Abstract: This work investigated the influence of N fertilization and grain maturity on total phenolic concentration (TPC) of wheat caryopses. A pot experiment was conducted, using soft spring wheat ( Triticum aestivum cv. Thasos) which was treated with four different amounts of nitrogen (0.25–2.00 g N pot −1 ) and harvested at three different development stages (medium milk stage, late milk stage, and dough maturity). Phenolic compounds were extracted and analyzed as total phenolic concentration in three discrete fractions: free soluble, conjugated soluble and insoluble bound forms. TPC of free phenolic compounds rose with increasing N supply while TPC of conjugated soluble phenolics decreased at the same time. Insoluble phenolics were less affected by N treatment. Total phenolic concentration also changed with the development stage of caryopses and reached a peak at the late milk stage.